Species-Specific Identification of a Wide Range of Clinically Relevant Fungal Pathogens by Use of Luminex xMAP Technology - Christine Landlinger; Sandra Preuner; Birgit Willinger; B. Haberpursch; Zdeněk Ráčil; Jiřı́ Mayer; Thomas Lion (2009)
ABSTRACT In immunocompromised patients suffering from invasive fungal infection, rapid identification of the fungal species is a prerequisite for selection of the most appropriate antifungal treatment. We present an assay permitting reliable identification of a wide range of clinically relevant fungal pathogens based on the high-throughput Luminex microbead hybridization technology. The internal transcribed spacer (ITS2) region, which is highly variable among genomes of individual fungal species, was used to generate oligonucleotide hybridization probes for specific identification. The spectrum of pathogenic fungi covered by the assay includes the most commonly occurring species of the genera Aspergillus and Candida and a number of important emerging fungi, such as Cryptococcus, Fusarium, Trichosporon, Mucor, Rhizopus, Penicillium, Absidia, and Acremonium . Up to three different probes are employed for the detection of each fungal species. The redundancy in the design of the assay should ensure unambiguous fungus identification even in the presence of mutations in individual target regions. The current set of hybridization oligonucleotides includes 75 species- and genus-specific probes which had been carefully tested for specificity by repeated analysis of multiple reference strains. To provide adequate sensitivity for clinical application, the assay includes amplification of the ITS2 region by a seminested PCR approach prior to hybridization of the amplicons to the probe panel using the Luminex technology. A variety of fungal pathogens were successfully identified in clinical specimens that included peripheral blood, samples from biopsies of pulmonary infiltrations, and bronchotracheal secretions derived from patients with documented invasive fungal infections. Our observations demonstrate that the Luminex-based technology presented permits rapid and reliable identification of fungal species and may therefore be instrumental in routine clinical diagnostics.